Dynamic beam shaping—Improving laser materials processing via feature synchronous energy coupling - Schmidt, Michael; Cvecek, Kristian; Duflou, J.; Vollertsen, F.; Arnold, C. B.; Matthews, M. J. (CIRP Annals - Manufacturing Technology, 2024)
Today, tailored laser beams are rarely used and thus an opportunity to optimize existing or introduce new processes is missed. New methods of dynamic beam shaping have the potential to change that in future. This keynote paper deals with methods allowing a transient energy input into the workpiece at such time scales that the underlying interaction processes are guided towards the desired result. It shows principles, categorizes necessary system technology, and gives application examples to familiarize the reader with the topic. It postulates that time-scale-dependent coupling between transient energy input and addressed process features is key for achieving the optimum.
CRIS-Team Scopus Importer:2024-08-23
Keywords: Adaptive control; Beam shaping; Laser